Pengaruh Punishment dan Pengawasan terhadap Disiplin Kerja dan Lama Bekerja sebagai Variabel Kontrol - Kalai Wanen; Bagus Handoko; Sunaryo Sunaryo (Universitas Harapan Medan, 2021)
This study aims to determine the effect of punishment on work discipline, the effect of supervision on work discipline, length of work on work discipline. The population in this study were 163 non-permanent teachers and permanent teachers at the Medan Raksana Education Foundation, and the sample taken was 116 using the Slovin formula. The data analysis technique used is multiple linear regression, hypothesis testing and the coefficient of determination. The results showed that punishment does not have a significant effect on work discipline, supervision has a significant effect on work discipline, length of work as a control variable has a significant effect on the punishment variable and supervision on work discipline.